The effect of financial literarture on interest in using fintech payment (paylater) in Shope (case study of Febi UINSU students) - Shahira Azmi; Hendra Harmain (Enrichment : Journal of Management, 2022)
This study aims to determine how big the literacy level is on the interest in using fintech payment payleter shopee products in FEBI UINSU students. The research method used is a quantitative method. The data collection in this study used a questionnaire distributed via google form with the respondents being FEBI UINSU students with study programs: Sharia Accounting, Sharia Banking, Sharia Insurance, Sharia Economics and Management. The sample in this study used the purposive sampling technique. In this study, the data analysis technique used is descriptive analysis and simple regression analysis using SPSS 26. The data collection in this study used a questionnaire method with the Likert scale method and distributed to 100 respondents. The results of this study indicate that there is a positive and significant influence between financial literacy on interest in using fintech payment paylater products at Shopee